정부의 사회서비스 공공성 강화전략과 입법과제 - 윤석진(Yoon Seok-Jin) (사회복지법제연구, 2018)
본 논문에서는 사회서비스원 또는 사회서비스공단 설치로 예견되는 복지환경변화와 이에따른 문제, 민간 사회복지법인 및 시설 등의 기능과 역할 재편전략을 살펴보았다. 이를 위해정부의 사회서비스 공공성 강화전략과 국회에서 심사 중인 관련 법안을 심층 검토하였다. 본 논문에서는 사회서비스원 또는 사회서비스공단의 설립을 둘러싼 국내 복지환경에 변화에 대응하기 위한 민간 사회복지법인 및 시설의 생존전략을 모색하였다. 그리고 정부정책 및관련 법률의 내용을 중심으로 그 문제점을 밝히고, 개선의 필요성을 제시하였다. 특히 국내사회서비스 분야가 공공과 민간으로 분리되는 현상에 착안하여 「사회복지사업법」의 전향적개선을 통한 민간 사회복지법인 및 시설의 경쟁력 확보방안을 구상해보았다. 그 결과, 본 논문에서는 사회서비스원 또는 사회서비스공단 시대 복지제공 주체 간의 공생방안을 핵심으로 정부 주도의 사회서비스 직접 운영을 자제하고 보장국가론의 관점에서 사회서비스 분야의 민⋅관 경쟁체제 도입을 주장했다. 그리고 구체적 방법으로 「사회복지사업법」 에 네거티브 규제의 도입, 협력적 복지거버넌스로의 체제전환, 규제수용도 개선을 위한 민간사회복지법인 및 시설 지원체계로의 개편 방안을 도출해 보았다. In this paper, we examined the changes in the welfare environment and the corresponding problems, functions and roles of private social welfare corporations and facilities, which are expected by the establishment of “The Social Service” or “The Social Service Public Corporation”. For this reason, the government's social service publicity strengthening strategy and related bills under consideration by the National Assembly were reviewed in depth. In this paper, we sought a strategy for survival of private social welfare corporations and facilities in response to changes in the domestic welfare environment surrounding the establishment of “Social Service” or “The Social Service Corporation”. It also revealed the problem with the contents of government policies and related laws and suggested the need for improvement. In particular, a measure was devised to secure competitiveness of private social welfare corporations and facilities through forward-looking improvement of 「Social Welfare Service Act」 in light of the current separation of the social services sector into the public and private sector. As a result, this paper advocated the introduction of a civil and government competition system in the field of social services from the perspective of a guaranteed national theory, while refraining from direct operation of government-led social services as the core of the social service provider. In specific ways, we drew up measures to introduce negative regulations, to change the system into a cooperative welfare governance, and to reform the private social welfare corporation and facility support system to improve regulatory acceptance in 「Social Welfare Service Act」. KCI Citation Count: 3